Measles-Rubella Vaccination: Epidemiological Issue, Immunology, and Ethical Challenges - Ainurafiq, Ainurafiq; Asrianti, Tanti; Sartika, Sartika; Salim, Eman Salim Ahmed; Indar, Indar (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
This article discusses issues related to measles-rubella vaccination from the perspective of epidemiology, immunology, and ethical challenges faced. Measles and rubella are infectious diseases that have the potential to cause extraordinary events (KLB) throughout the world, including Indonesia. Although measles-rubella vaccination has been proven effective in reducing the incidence of the disease, challenges such as low vaccination coverage due to the COVID-19 pandemic, vaccine hesitancy, and ethical issues related to parental consent and equal access to vaccines are significant obstacles. Research shows that to achieve effective community immunity, a vaccination coverage of at least 95% is required. This article also describes the immunological processes involved in the response to measles and rubella infection and the importance of public health efforts in increasing awareness and access to vaccines. With a comprehensive and inclusive approach, it is hoped that existing challenges can be overcome and community participation in vaccination programs can be increased. Collaboration between the government, health institutions, and the community is essential to create a healthier and safer environment, ultimately supporting the goal of eliminating measles and rubella in the future.